Treatment Patterns and Outcomes of Anastomotic Leakage after Esophagectomy for Esophageal Cancer - Hyo Won Seo; Yeong Jeong Jeon; Jong Ho Cho; Hong Kwan Kim; Yong Soo Choi; Jae Ill Zo; Young Mog Shim (Journal of Chest Surgery, 2024)
Background: Anastomotic leakage (AL) following esophagectomy represents a serious complication that often results in prolonged hospitalization and necessitates repeated interventions, including nothing-by-mouth (NPO) restriction, endoscopic vacuum therapy (EVT), or surgical repair. In this study, we evaluated the patterns and outcomes of AL treatment. Methods: We retrospectively reviewed the medical records of patients who underwent esophagectomy for esophageal cancer at a single center between 2003 and 2020. Of 3,096 examined cases, 181 patients (5.8%) with AL were included in the study: 114 patients (63%) with cervical anastomosis (CA) and 67 (37%) with intrathoracic anastomosis (TA). Results: The incidence of AL was 11.9% in the CA and 3.2% in the TA group (p<0.001). Among patients with CA who developed AL, 87 (76.3%) were managed with NPO, 15 (13.2%) with EVT, and 12 (10.5%) with surgical repair. Over 90% of patients with cervical AL resumed an oral diet by the time of discharge, regardless of treatment method. Among patients with TA and AL, 36 (53.7%) received NPO, 25 (37.7%) underwent EVT, and 6 (9%) required surgery. Of these, 34 patients who were managed with NPO and 19 with EVT could resume an oral diet. However, only 2 patients who underwent surgery resumed an oral diet, and 2 patients required additional EVT. Conclusion: Although patients with CA displayed a higher incidence of AL, their rate of successful oral intake exceeded that of those with TA, regardless of treatment method. Among patients exhibiting AL with TA, EVT was more commonly employed than in CA cases, and it appears effective.